Human cytomegalovirus escapes immune recognition by NK cells through the downregulation of B7-H6 by the viral genes US18 and US20 - Yoav Charpak-Amikam (Nature Portfolio, 2017)
Abstract Human cytomegalovirus (HCMV) is a major human pathogen, causing serious diseases in immunocompromised populations and congenially infected neonates. One of the main immune cells acting against the virus are Natural Killer (NK) cells. Killing by NK cells is mediated by a small family of activating receptors such as NKp30 that interact with the cellular ligand B7-H6. The outcome of B7-H6-NKp30 interaction was, so far, mainly studied with regard to NK recognition and killing of tumors. Here, we demonstrated that the expression of B7-H6 is upregulated following HCMV infection and that HCMV uses two of its genes: US18 and US20, to interfere with B7-H6 surface expression, in a mechanism involving endosomal degradation, in order to evade NK cell recognition.